2019
DOI: 10.7759/cureus.5338
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism Manifesting as a Combination of Ascites and Malnutrition Requiring Total Parenteral Nutrition: A Unique Presentation

Abstract: Ascites is the abnormal buildup of fluid in the abdomen. Despite appropriate workup, including diagnostic paracentesis with fluid analysis and abdominal imaging, the cause of ascites is sometimes unknown. In this case, testing for less common causes should be performed, including checking thyroid function test (TFT) because hypothyroidism has also been reported to be a rare cause of ascites. Patients may also have concomitant malnutrition as an effect of severe hypothyroidism, rather than as its cause. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…These values are similar to our study, although only individuals with DS and hypothyroidism were included. However, several studies reported no decrease in the z-score of the nutritional status as a result of hypothyroidism 28 . The hypothyroid condition is a hypometabolic state in which the basal metabolic rate (BMR) decreases 29,30 , hence, some individuals with hypothyroidism experience excess nutrients rather than a lack 31 .…”
Section: Resultsmentioning
confidence: 99%
“…These values are similar to our study, although only individuals with DS and hypothyroidism were included. However, several studies reported no decrease in the z-score of the nutritional status as a result of hypothyroidism 28 . The hypothyroid condition is a hypometabolic state in which the basal metabolic rate (BMR) decreases 29,30 , hence, some individuals with hypothyroidism experience excess nutrients rather than a lack 31 .…”
Section: Resultsmentioning
confidence: 99%